Comparing moment redistribution in statically indeterminate reinforced concrete beams with and without corrosion - A. G. Tamrazyan; Yehia Ahmed Kotp Sayed (Vestnik MGSU)
Introduction. The actual question of redistribution of moments in statically indeterminate reinforced concrete (RC) beams subjected to corrosion is considered. Statically indeterminate RC beams are widely used in various construction applications, and understanding how corrosion affects the redistribution of moments in such beams is important for assessing their load-bearing capacity and safety. Experimental and analytical methods are applied to study the effect of corrosion on the redistribution of moments in RC beams.Materials and methods. To carry out this investigation, a new technique was implemented to accelerate and control the corrosion process, applied according to the experimental programme. Four two-span reinforced concrete beams, both with and without induced corrosion, were subjected to bending moments in the experimental setup. The methods involved careful application of corrosion, and the experimental programme aimed to simulate real-world conditions.Results. The experimental results were compared for the beams with and without corrosion. The analysis revealed significant effects of corrosion on the redistribution of moments in statically indeterminate reinforced concrete beams. Furthermore, the degree of corrosion was found to be directly proportional to the increased redistribution of moments. Moreover, the proposed model can significantly determine the redistribution coefficient of moments in statically indeterminate RC beams.Conclusions. This study highlights the significant influence of corrosion on the redistribution of moments in statically indeterminate reinforced concrete beams. The results obtained show that as the corrosion percentage increases, there is a corresponding increase in the redistribution of moments. The results obtained can provide a basis for the development of future strategies to reduce the effects of corrosion on statically indeterminate reinforced concrete beams, thereby improving structural design and construction practices.